Totality and dialectics. The concept of totality in Adorno and Hegel - Charry Bermúdez, Manuel Ernesto (Estudios de Filosofía, 2017)
This paper seeks to expose critically some fundamental contents of the concept of totality and its importance to dialectical thinking. Starting from a critique of Hegel’s conception of totality it seeks, however, to defend this concept but reconstructed to a materialistic turnaround, just as it was developed in the philosophy of Theodor W. Adorno. The concept of totality would change its meaning and function through a materialistic critique, moving from the idea of a determined and definitive whole, to an epistemic and normative criterion to counter effectively the imposition of a social totality.